Implementation Of Work Discipline On The Productivity Of Civil Servants (BKPSDM Bekasi Regency) - Ghifari Abimanyu; Fereshti Nurdiana Dihan (International Journal of Economics, Business and Innovation Research, 2025)
This study examines the implementation of work discipline on employee productivity at the Bekasi Regency Personnel and Human Resource Development Agency (BKPSDM), prompted by issues such as tardiness and non-compliance with dress codes. A qualitative approach was employed, using observation, semi-structured interviews with six informants, and documentation (February-June 2023, May 2025). Findings reveal that the GPS-based attendance system is hindered by signal issues, with personal awareness as the main barrier. Theoretical review highlights the link between discipline and productivity, along with preventive-corrective approaches. Discussion suggests optimizing technology and enforcing strict sanctions. Conclusion: enhanced work discipline can boost productivity, with recommendations including infrastructure improvements, sanctions, and training.